2017
DOI: 10.15406/ijrrt.2017.03.00048
|View full text |Cite
|
Sign up to set email alerts
|

Success, Effectiveness and Safety of Combined Sonographic and Fluoroscopic Guided Percutaneous Nephrostomy in Malignant Ureteral Obstruction

Abstract: Introduction: Percutaneous nephrostomy (PCN) is a palliative procedure required to drain malignant ureteral obstruction to provide reasonable benefit to the patient. The study was conducted with the objective to assess the success, effectiveness and safety of combined USG and Fluoroscopy guided percutaneous nephrostomy in malignant ureteral obstruction.Method: 69 obstructed ureters due to malignant cause in 50 patients were drained by PCN using combined ultrasound (USG) and fluoroscopic guidance. Postprocedura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Regarding the causes of OU, many literatures showed that most cases are secondary to lower urinary tract pathologies which are primarily malignant. 11,21 Our study also showed a similar finding in which more than 80% of the obstructive pathologies were caused by pelvic malignancies and the ureter was essentially the commonest part of urinary tract involved (77%).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Regarding the causes of OU, many literatures showed that most cases are secondary to lower urinary tract pathologies which are primarily malignant. 11,21 Our study also showed a similar finding in which more than 80% of the obstructive pathologies were caused by pelvic malignancies and the ureter was essentially the commonest part of urinary tract involved (77%).…”
Section: Discussionsupporting
confidence: 80%
“…Some studies reported image-guided PCN to be performed in males more commonly than in females while other studies showed females with OU to be commonly encountered during this procedure. 1,16,[18][19][20][21] Our study shows a female predominance (70%), which is partly explained by the finding that cervical cancer is the commonest cause of OU in this study (37.3%) and more than 50% of OU patients with bladder cancer were females. However, being male was associated with an increased likelihood of successful outcome of emergency PCN [AOR = 5.72 (1.13-28.92) at 95% CI; p = 0.035].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Less commonly usage of CT can be used especially in abnormal anatomy, ectopic kidney and transplanted kidney (4) Contrast enhanced US can be used in non-dilated kidneys (5). Combined use of ultrasound and fluoroscopy is expected to achieve better results in terms of success rate and decrease in the occurrence of major complications of percutaneous nephrostomy insertion (6). US alone can be used safely in PCN insertion in case of marked dilatation of pelvicalyceal system especially in one stab technique and also can be used in puncture and dilatation in cases of pregnancy or hypersensitivity to contrast material but by well experienced surgeons (3).…”
Section: Introductionmentioning
confidence: 99%